Disrupting of IGF2BP3-stabilized CLDN11 mRNA by TNF-α increases intestinal permeability in obesity-related severe acute pancreatitis - Lihui Lin; Yansong Lin; Xianwen Guo; Ruoyi Zhang; Xin Ling; Zewen Zhang; Rong Lin; Zhen Ding (Molecular Medicine)
Abstract Background Obesity is a significant risk factor for severe acute pancreatitis (SAP) and is typically associated with increased intestinal permeability. Understanding the role of specific molecules can help reduce the risk of developing SAP. Claudin 11 (CLDN11), a member of the Claudin family, regulates the permeability of various internal barriers. However, the role and mechanism of CLDN11 in the intestinal permeability of obesity-related SAP remain unclear. Methods We evaluated intestinal permeability and the expression of CLDN11 in experimental obesity-related SAP. A recombinant adeno-associated virus carrying CLDN11 was used to treat experimental obesity-related SAP. The interaction between CLDN11 mRNA and insulin-like growth factor 2 mRNA-binding protein 3 (IGF2BP3) protein was predicted through bioinformatics analysis and validated by RNA immunoprecipitation and RNA pull-down assay. Additionally, tumor necrosis factor-α (TNF-α) treatment in Caco-2 cells was conducted, and the IGF2BP3/CLDN11 axis was detected. Moreover, we conducted anti-TNFα therapy and evaluated intestinal permeability and pancreatic inflammation in experimental obesity-related SAP. Results Downregulation of CLDN11 was observed in the intestinal epithelial cells of experimental obesity-related SAP. When the expression of CLDN11 in intestinal epithelial cells of experimental obesity-related SAP was increased exogenously, intestinal epithelial permeability and pancreatic inflammation were relieved. Overexpression of CLDN11 reduced the paracellular permeability of Caco-2 monolayer cells, while knockdown of CLDN11 increased it. IGF2BP3 bound to and regulated the stability of CLDN11 mRNA. TNF-α treatment downregulated IGF2BP3 and CLDN11 in vitro. Anti-TNFα therapy reduced intestinal permeability, alleviated pancreatitis, and improved the expression of IGF2BP3 and CLDN11 in intestinal epithelial cells in experimental obesity-related SAP. Conclusion CLDN11 regulates intestinal permeability in obesity-related SAP. Mechanistically, an increase in TNF-α impaired the stability of IGF2BP3-dependent CLDN11 mRNA in obesity-related SAP.